Mechanically rollable photodetectors enabled by centimetre-scale 2D MoS2 layer/TOCN composites. Issue 11 (26th April 2021) - Yoo, Changhyeon; Ko, Tae-Jun; Han, Sang Sub; Shawkat, Mashiyat Sumaiya; Oh, Kyu Hwan; Kim, Bo Kyoung; Chung, Hee-Suk; Jung, Yeonwoong
Abstract : Wafer-scale CVD-2D MoS2 layers integrated on cellulose TOCN substrates are configured into rollable 3D forms. These MoS2 /TOCN composites exhibit intriguing photo-responsiveness unattainable with traditional photodetectors of fixed physical forms. Abstract : Two-dimensional (2D) molybdenum disulfide (MoS2 ) layers are suitable for visible-to-near infrared photodetection owing to their tunable optical bandgaps. Also, their superior mechanical deformability enabled by an extremely small thickness and van der Waals (vdW) assembly allows them to be structured into unconventional physical forms, unattainable with any other materials. Herein, we demonstrate a new type of 2D MoS2 layer-based rollable photodetector that can be mechanically reconfigured while maintaining excellent geometry-invariant photo-responsiveness. Large-area (>a few cm 2 ) 2D MoS2 layers grown by chemical vapor deposition (CVD) were integrated on transparent and flexible substrates composed of 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized cellulose nanofibers (TOCNs) by a direct solution casting method. These composite materials in three-dimensionally rollable forms exhibited a large set of intriguing photo-responsiveness, well preserving intrinsic opto-electrical characteristics of the integrated 2D MoS2 layers; i.e., light intensity-dependent photocurrents insensitive to illumination angles as well as highly tunable photocurrents varying with the rolling number of 2D MoS2 layers, which were impossible to achieve with conventional photodetectors. This study provides a new design principle for converting 2D materials to three-dimensional (3D) objects of tailored functionalities and structures, significantly broadening their potential and versatility in futuristic devices.